Using Habitat, Morphological, and Genetic Characteristics to Delineate the Subspecies of Sharp‐Tailed Grouse in South‐Central Wyoming - Jonathan D. Lautenbach; Andrew J. Gregory; Stephanie Galla; Aaron C. Pratt; Michael A. Schroeder; Jeffrey L. Beck (Ecology and Evolution)
ABSTRACT Identifying species and subspecies is the foundation for focusing conservation efforts and studying evolutionary ecology. Subspecies delineation has occurred using multiple data types, including ecological, morphological, and genetic data. There are currently seven recognized Sharp‐tailed Grouse (Tympanuchus phasianellus, Linnaeus, 1758) subspecies, with two of these subspecies occurring in Wyoming: Columbian Sharp‐tailed Grouse (T. p. columbianus) and plains Sharp‐tailed Grouse (T. p. jamesi). There is a third population of Sharp‐tailed Grouse in south‐central Wyoming with an unknown subspecific identification. Historically, this population has been classified as Columbian Sharp‐tailed Grouse; however, previous genetic evidence questioned this classification. To better understand the subspecific status of this south‐central Wyoming population, our study used habitat characteristics, morphological characteristics, and genetic data (microsatellite loci and single nucleotide variants) collected from known Columbian Sharp‐tailed Grouse, known plains Sharp‐tailed Grouse, and the south‐central Wyoming population of Sharp‐tailed Grouse. We modeled differences among the populations using discriminant analysis of principal components and Random Forests classification models. Across all four datasets and both modeling techniques, we found that each population (Columbian Sharp‐tailed Grouse, plains Sharp‐tailed Grouse, and south‐central Wyoming population of Sharp‐tailed Grouse) generally represented its own cluster. Our results suggest that the population of Sharp‐tailed Grouse in south‐central Wyoming is different from both Columbian and plains Sharp‐tailed Grouse. We recommend further evaluation of the subspecies of Sharp‐tailed Grouse using more targeted phylogenomic studies to identify if Sharp‐tailed Grouse in south‐central Wyoming represent a separate subspecies or are a distinct population of another subspecies. Our results potentially change our understanding of Columbian Sharp‐tailed Grouse distribution and management and highlight the importance of using a more comprehensive approach to identifying subspecies.